The life and work of Margaret Gatty (1809–1873), with particular reference to her seaweed collections. Issue 2 (October 2016) - Plaisier, H.; Bryant, J. A.; Irvine, L. M.; Mclean, A.; Jones, M.; Spencer Jones, M. E.
Abstract : Margaret Gatty was a skilled seaweed collector. Her large worldwide collection currently housed at St Andrews University Herbarium and another significant collection (of both seaweeds and marine invertebrates) held at Museums Sheffield are evaluated for the first time. These collections have remained largely un-curated, but assessment and data capture of their holdings is currently under way. Mrs Gatty acquired great skill and expertise as a collector and student of seashore flora and fauna, so much so that a number of taxa were named after her. Her daughter, Horatia, followed her mother but specialised in marine invertebrates, amassing a large collection, the bulk of which is divided between Sheffield and the Natural History Museum, London. An appendix of taxa associated with Mrs Gatty is included.